2002
DOI: 10.1038/sj.gt.3301711
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral transduction of human T-lymphocytes with a RANTES intrakine inhibits human immunodeficiency virus type 1 infection

Abstract: Intrakines, modified intracellular chemokines, offer a novel strategy to prevent cellular entry of HIV-1 by blocking the surface expression of HIV-1 co-receptors. To investigate potential clinical applications of the RANTES-intrakine, we explored the use of HIV-1-based lentiviral vectors for therapeutic gene transfer into T-lymphocytes. RANTES-intrakine genes can be efficiently transduced into primary human Tlymphocytes by lentiviral vectors, especially when human Tlymphocytes were stimulated with CD3 and CD28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 47 publications
(46 reference statements)
1
32
0
Order By: Relevance
“…21 It was also reported that neutralizing antibody to SDF-1 decreased the proliferation of bone-homing metastatic prostate cancer cells. 14 Most recently, Zeelenberg et al 25 reported that blocking the surface expression of CXCR4 with an ''intrakine'', developed in our laboratory, 23,24 greatly reduced the ability of CT26 colon cancer cells to metastasize to the liver and lungs. This effect was not attributed to the inhibition of tumor cell invasion, but rather to the impairment of outgrowth of micrometastases.…”
Section: Cxcr4 Knockdown Abrogates Breast Tumor Growth N Lapteva Et Almentioning
confidence: 97%
“…21 It was also reported that neutralizing antibody to SDF-1 decreased the proliferation of bone-homing metastatic prostate cancer cells. 14 Most recently, Zeelenberg et al 25 reported that blocking the surface expression of CXCR4 with an ''intrakine'', developed in our laboratory, 23,24 greatly reduced the ability of CT26 colon cancer cells to metastasize to the liver and lungs. This effect was not attributed to the inhibition of tumor cell invasion, but rather to the impairment of outgrowth of micrometastases.…”
Section: Cxcr4 Knockdown Abrogates Breast Tumor Growth N Lapteva Et Almentioning
confidence: 97%
“…Intratumoral injection of adenoviral vector encoding macrophage-derived chemokine (MDC, CCL22) resulted in marked tumor regression of Lewis lung carcinoma through strong chemoattracting activity of dendritic cells (DC), NK cells, and T lymphocytes [16]. Gene transfer of another CC chemokine, RANTES (CCL5) [17], or of the C chemokine lymphotactin (XCL1) [18] also exhibited strong antitumor activity in solid tumor models. These results suggested that chemokines could mediate innate and adaptive antitumor immune response by recruiting monocytes, DC, NK, and T lymphocytes into tumor sites.…”
Section: Introductionmentioning
confidence: 99%
“…Some chemokines induce angiogenesis and thus promote tumor growth and metastasis [14,15]. However, tumor suppression by chemokine gene transfer into tumor cells has been demonstrated in animal models [16][17][18]. Intratumoral injection of adenoviral vector encoding macrophage-derived chemokine (MDC, CCL22) resulted in marked tumor regression of Lewis lung carcinoma through strong chemoattracting activity of dendritic cells (DC), NK cells, and T lymphocytes [16].…”
Section: Introductionmentioning
confidence: 99%
“…This mutant protein is one of the most potent inhibitors of HIV replication. Intracellular antibodies and intrakines have also proven to be very potent inhibitors of HIV replication [42][43][44][45][46] . These proteins work by binding to viral or cellular target proteins, most often resulting in targeting of the proteins to the proteasome for degradation.…”
Section: Protein-based Inhibitorsmentioning
confidence: 99%